2019
DOI: 10.1080/02723646.2019.1706215
|View full text |Cite
|
Sign up to set email alerts
|

CFD flow dynamics over model scarps and slopes

Abstract: As sea level rises, and during storm and surge events, coastal dunes may become cliffed or scarped by wave action. Knowledge of wind flow over dune scarps, and as scarps fill, their subsequent various slopes, is an essential first step to understanding sediment transport pathways from the beach to the dunes. In this study, flow over scarps (also termed forward facing steps) is reviewed, and the flow over a vertical scarp (90°) and three slopes of 45°, 24° and 14°, all 2 m in height, is examined via CFD modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 81 publications
4
30
0
Order By: Relevance
“…For instance, during post‐storm recovery scarps fill up by wind‐blown sand deposited at the dune foot, building a so‐called dune ramp (e.g., Carter et al., 1990, Ollerhead et al., 2013), altering sediment transport and deposition patterns across the foredune. Previous studies used numerical models to compare flow deflection across a scarped and nonscarped foredune, with uncertain implications on dune recovery (Hesp & Smyth, 2016a, 2019; Piscioneri et al., 2019). Volumetric field observations led to conceptual insights, showing that a dune ramp has a major impact on sand transported to the dune crest and lee slope, where scarped dunes devoid of a dune ramp show significantly reduced crest directed transport (Castelle et al., 2017; Christiansen & Davidson‐Arnott, 2004; Donker et al., 2018; Ollerhead et al., 2013; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, during post‐storm recovery scarps fill up by wind‐blown sand deposited at the dune foot, building a so‐called dune ramp (e.g., Carter et al., 1990, Ollerhead et al., 2013), altering sediment transport and deposition patterns across the foredune. Previous studies used numerical models to compare flow deflection across a scarped and nonscarped foredune, with uncertain implications on dune recovery (Hesp & Smyth, 2016a, 2019; Piscioneri et al., 2019). Volumetric field observations led to conceptual insights, showing that a dune ramp has a major impact on sand transported to the dune crest and lee slope, where scarped dunes devoid of a dune ramp show significantly reduced crest directed transport (Castelle et al., 2017; Christiansen & Davidson‐Arnott, 2004; Donker et al., 2018; Ollerhead et al., 2013; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, CFD has helped to substantially advance our understanding of airflow dynamics over dunes (Smyth, 2016; Walker et al, 2021). The formation of helicoidal flow has been examined using flow streamlines in CFD, utilizing post‐processing to provide three‐dimensional visualizations (Hesp & Smyth, 2019; Jackson et al, 2013; Wakes et al, 2021). To date, however, the characteristics of helicoidal flow, including the response to variations in wind speed, have barely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the k – ε RNG turbulence model modelled wind flow well, compared with field observations, over complex dune landforms such as a foredune (Hesp et al, 2015; Pattanapol et al, 2011; Wakes et al, 2010), blowouts (Smyth et al, 2012, 2019) and parabolic dunes (Delgado‐Fernandez et al, 2018; Smyth et al, 2020; Wakes et al, 2016). A second‐order spatial discretization scheme was employed to interpolate values between cell centres, and calculations were considered complete once the initial residual of each iteration was <0.0001 m s −1 for U X , U Y and U Z (Hesp & Smyth, 2019).…”
Section: Methodology and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, flow–form–sand transport interactions have been studied on various coastal dune landforms, including foredunes (de Winter et al, 2020; Delgado‐Fernandez et al, 2013; Hesp & Smyth, 2016; Hilton et al, 2016; Jackson et al, 2013, 2011; Lynch, Jackson, & Cooper, 2009; Lynch, Jackson, & Cooper, 2010; Petersen, Hilton, & Wakes, 2011; Schwarz et al, 2021; Wakes, Bauer, & Mayo, 2021; Wakes, Hilton, & Konlechner, 2016; Wakes et al, 2010; Walker et al, 2017), foredune scarps (Hesp & Smyth, 2019; Piscioneri, Smyth, & Hesp, 2019), blowouts (Garès & Pease, 2015; Hesp & Walker, 2012; Hugenholtz & Wolfe, 2009; Pease & Gares, 2013; Smyth, Jackson, & Cooper, 2012; Smyth, Jackson, & Cooper, 2013; Smyth et al, 2019; Smyth, Jackson, & Cooper, 2014), parabolic dunes (Anderson & Walker, 2006; Delgado‐Fernandez et al, 2018; Hansen et al, 2009; Smyth et al, 2020; Wakes, 2013), nebkha (Hesp & Smyth, 2017; Zhao et al, 2019, 2020, 2021), sand cays (Hilton et al, 2019), beaches with large woody debris (Grilliot, Walker, & Bauer, 2018; Grilliot, Walker, & Bauer, 2019), and beach scarped ridges (Smyth & Hesp, 2015). These studies have contributed to our understanding of flow–form–sand transport relationships in a wide range of aeolian situations.…”
Section: Introductionmentioning
confidence: 99%